2019
DOI: 10.1080/19476337.2018.1544591
|View full text |Cite
|
Sign up to set email alerts
|

Integrated solvent-free extraction and encapsulation of lutein from marigold petals and its application

Abstract: Vivid orange petals of marigold have been studied well as the richest source of lutein. Although it is very promising to be explored as functional food ingredients, there were only few studies that described extraction methods which meet food grade requirements. Here, lutein was extracted from marigold petals using vegetable oil, subsequently encapsulated and prepared as lyophilized powder, and incorporated into milk-tea beverage. An organoleptic assay was conducted in order to evaluate the effect of lutein ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For instance, the highest lutein content of 10.3 mg/g extracted from dry marigold petals utilising supercritical fluid extraction with soyabean oil as a co-solvent was reported by Ma et al, 2008 [39] . A more recent study reported that the amount of lutein extracted from marigold petals using edible oil was 1.9 times higher than that extracted by using acetone and almost equal to that of extracted by hexane [11] . Higher content of lutein (20.71 mg /g db of marigold flower petals) was reported while extracting and de-esterifying lutein simultaneously using the mixture of liquefied dimethyl ether (DME), KOH, and EtOH [4] .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, the highest lutein content of 10.3 mg/g extracted from dry marigold petals utilising supercritical fluid extraction with soyabean oil as a co-solvent was reported by Ma et al, 2008 [39] . A more recent study reported that the amount of lutein extracted from marigold petals using edible oil was 1.9 times higher than that extracted by using acetone and almost equal to that of extracted by hexane [11] . Higher content of lutein (20.71 mg /g db of marigold flower petals) was reported while extracting and de-esterifying lutein simultaneously using the mixture of liquefied dimethyl ether (DME), KOH, and EtOH [4] .…”
Section: Resultsmentioning
confidence: 95%
“…Lutein has been extracted from marigold petals using both conventional(simple maceration, soxhlet extraction) and novel methods (supercritical fluid extraction enzyme-assisted extraction, microwave-assisted extraction [9] , [10] . However conventional methods are equipped with enormous disadvantages like longer extraction times, high quantity of solvents used and heat degradation of carotenoids [11] . To overcome this challenge, several steps have been taken by researchers to ensure greener, sustainable and viable techniques for lutein extraction.…”
Section: Introductionmentioning
confidence: 99%
“…In canola oil, lutein esters can be extracted without solvents from marigold petals to obtain lutein pigment. Extraction with oil yielded roughly twice as much as acetone and nearly as much as n-hexane, showing that it can reduce process costs while improving product safety (Indrawati et al, 2019). For extracting lutein diester from the marigold meal, lutein diester and lipophilic material are dissolved in supercritical fluid carbon dioxide at specific temperatures and pressures, followed by the separation of a high-quality lutein diester extract (Rao and Reddy, 2003).…”
Section: Lutein Extraction From Marigoldmentioning
confidence: 99%
“…They are an important source of lutein. It was found that marigold flowers contain lutein content at around 70% of the carotenoid content [ 1 , 2 ]. Lutein is an excellent antioxidant that is used in the food, cosmetic, and pharmaceutical industries [ 1 ].…”
Section: Introductionmentioning
confidence: 99%